Development of food and beverage service module at vocational high schools culinary service expertise program - Anugrah, Ajeng Inggit (Universitas Negeri Padang, 2021)
This article aims to explain that the study was to develop a learning module on the subjects of Food and Beverage Services for students majoring in food services at SMK Putra Anda Binjai. This study was Research and Development (R & D) using the ADDIE development model. The results of research and development done in this study indicate that the validation results by learning modules covering material expert’s feasibility content with value Aiken's V = 0.78 valid criteria, eligibility presentation of Aiken's V = 0.80 on valid criteria, aspects of language with Aiken's V = 0.8 on valid criteria, and validation of design experts with Aiken's V = 0.80 on valid criteria. Test practitioners learning modules to two teachers showed an average yield of 81.67 in the category of